Mitochondrial Transplantation: A Novel Therapeutic Approach for Treating Diseases - Xinglu Miao; Pei Jiang; Zhaoping Wang; Weihua Kong; Lei Feng (MedComm)
ABSTRACT Advances in mitochondrial biology have led to the development of mitochondrial transplantation as a novel and promising therapeutic strategy. This review provides a comprehensive analysis of the multifaceted roles of mitochondria in health and disease, highlighting their central functions in energy production, antioxidant defense, calcium signaling, apoptosis regulation, and mitochondrial homeostasis maintenance. We explore the mechanisms by which transplanted mitochondria exert their therapeutic effects, including restoring ATP production, attenuating oxidative stress, modulating inflammatory responses, reducing cellular apoptosis, promoting cell repair and regeneration, facilitating neural circuit reconstruction, and exhibiting antitumor properties. Key preclinical studies demonstrating the efficacy of mitochondrial transplantation across in vitro and in vivo disease models are discussed, along with the status of clinical trials. The review also critically compares mitochondrial transplantation with other mitochondria‐targeted therapies, evaluating their relative advantages and limitations. Finally, we discuss the current challenges of translating this innovative therapy into clinical practice, such as mitochondrial isolation and purification, storage, targeted delivery, potential immune responses, and long‐term safety and efficacy concerns. This review aims to stimulate further research and development in this promising field, paving the way for novel therapeutic interventions for various diseases.